Rupture and Repair in Mentalization-Based Group Psychotherapy. Issue 2 (3rd April 2021) - Bateman, Anthony; Campbell, Chloe; Fonagy, Peter
ABSTRACT: The article explores ideas about the role of group mentalizing—the experience of joint attention and shared intentionality—as a process that can support the emergence of more collaborative and salutogenic social functioning. This is based on developmental and evolutionary thinking about the importance of joint attention in human social cognitive development and functioning. The importance of experiencing rupture and repair as part of the process of thinking together—while also working with the separate nature of our thoughts—is described, emphasizing that it is through an understanding of the complex and inevitably uneven and challenging nature of joint attention and social cooperation that such cooperation is itself made possible.